Pemberian Makanan Pendamping ASI (MP-ASI) dengan Kejadian Diare pada Bayi Usia 0-12 Bulan: Extra Breast Feeding Administered With Diarrhea Toward Babies 0-12 Months - Ni Ketut Kariani; Sri Indriningsi (Media Publikasi Cendekia Indonesia, 2023)
Background: Nowdays, Diarrhea still become main caused of sickness and mortality even toward babies and children. One of predisposition factor of dirrhea is extra breast feeding administered before 6 months in age. Aims: The aims of this research to obtain the correlation of extra breast feeding administered with diarrhea toward babies 0 12 months old in Lebiti Public Health Center (PHC), Togean Subdistrict. Methods: This is quantitative research with cross sectional approached. The total population about 214 of the women who have babies with 0 – 12 months old and got diarrhea disease experiences within last 2 years. The sampling only 61 women that taken by accidental sampling technique. The tools used by questioniarre and data analysed by chi-square test. Results: The result shown that have orrelation of extra breast feeding administered with diarrhea toward babies 0 12 months old in Lebiti Public Health Center (PHC), Togean Subdistrict of Tjo Una Una Regency with pvalue = 0,002. Conclusion: mother who give MP-ASI to babies regardless of age, frequency, portion, type, and method giving the right MP-ASI.